Demand Side Management and Voltage Control through Smart Inverter Enabled DER with Networked Micro-Grid System - Singh S.; Kumar R.; Das B.; Singh S.P. (My University, 2025)
The widespread installation of distributed energy resources (DER) across the electric power network infrastructure, especially in the distribution grid has emerged as opportunities and challenges for network operators to manage the operation and control of electric power systems. These DERs are leveraged with inverter-based resources that can unlock the potential benefits for distribution network management such as demand side management, voltage management, etc. In this context, this paper introduced smart inverter-based Volt/VArcontrol to deploy the conservation voltage regulation (CVR) in order to manage the load demand. A predictive model-driven scenario-based voltNAR control scheme to enable the CVR operation has been used. To check the effectiveness of CVR deployment, and communication-free, adjustive droop-based voltage control scheme based on local measurement has been introduced in coordination with a networked microgrid controller. Quick voltage support has been achieved by superimposing the responses of multiple inverter-based CMG controllers to mitigate the voltage fluctuations under transient events. The results of the simulations verify the suggested control scheme and show that CVR with CMG operation can significantly lower peak power demand. Additionally, the CMG controller system manages voltage regulation more intelligently than other controls. © 2024 IEEE.